Intelligence testing, ethnicity, and construction of the deviant child: Foucault and special education in Sweden - Thom Axelsson (Nordic Journal of Social Research)
In this article, I discuss how Foucault may help us to reach a different understanding of special education. This article primarily draws on two analytical tools from Foucault’s ‘toolbox’: genealogy and governmentality. These tools are used to analyse three different cases of intelligence testing from the debate concerning the Swedish school organization in the early twentieth century. It is possible to see intelligence-quotient (IQ) testing as an overarching tool for controlling social behaviour. Intelligence-quotient testing was an important tool of power, with the aim of establishing certain regimes of truth on a societal as well as on an individual level. This article shows through a Foucauldian analysis that we should be careful in interpreting this entirely as an expression of state power from above or as different experts’ intentions. Rather, by using a genealogical approach, we can attempt to (re)write the history of interpretations, or problematizations, and then we can utilize a perspective of governmentality that focuses on the techniques and their effects.